PENGEMBANGAN BUKU TEKS MITIGASI BENCANA PADA MATERI ERUPSI GUNUNG API DI SDN PENATARAN 01 KABUPATEN BLITAR - Meviana, Ika; Susanti, Nelya Eka (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2019)
In science subjects at the elementary school level, the concept of geologiâ€™s disaster can be introduced, such as disaster mitigation, namely volcanic eruption disaster. The purpose of this study was to determine the contents feasibility and the book presentation of disaster mitigation education material. In addition, the purpose of developing textbooks was to determine students' understanding of volcanic eruption disaster mitigation materials. This research was designed with a modified 4-D development design. The 4-D development design stages are Define, Design, Develop, and Disseminate. In this study the 4-D design was modified into three steps, namely: Define, Design, Develop. Based on the results of research and discussion, the feasibility of the contents and presentation of the book with Disaster Mitigation education material for grade 5 students after going through a series of processes including the validation from material experts, product presentation, language, graphics, limited trials, and field trials, the product is categorized of having very good quality. The level on students understanding of disaster mitigation education material of grade 5 books as a developed product is seen based on students cognitive and affective aspects. Based on the result of the student work on the post test sheet, the average value obtained by the students is 82,25, it incates that students learning process about the mitigation of volcanic eruption disaster have been completed. The dominant scientific attitude of students are curiosity, gaining new information, and cooperation. These scientific atitudes are reflectedÂ  in the activities of students who are interested in repeating the experiments and their harmonious work shown by the fact that they can work well together with friend within their group.Keywords: development; textbooks; disaster mitigation; volcanoes